A Renal Function Based Trade-Off Analysis of Non-vitamin K Antagonist Oral Anticoagulants in Nonvalvular Atrial Fibrillation - Zhou, Ling-Yun; Yang, Shuo-Fei; Zhang, Zhen; Zhang, Chi; Shen, Long; Gu, Zhi-Chun; Zuo, Xiao-Cong (Frontiers in Physiology, 2018)
Background Non-vitamin K antagonist oral anticoagulants (NOACs) depend on some degree of renal excretion, and no head-to-head comparisons based on renal function is available. This study mainly investigated the trade-off property of NOACs in nonvalvular atrial fibrillation (NVAF) with varying degrees of renal function. Methods 5 phase Ⅲ Clinical Trials comparing NOACs with warfarin in NVAF patients were included. Primary efficacy outcome was any Stroke or systemic embolism (S/SE). Major bleeding was considered as a primary safety outcome. Risk ratios (RRs) with their confidence intervals (CIs), the surface under the cumulative ranking curve (SUCRA), and trade-off analysis were conducted by renal function. Results A total of 72961 NVAF patients were included. In terms of normal renal function, dabigatran-150mg was ranked first for efficacy (SUCRA: 90.3), and edoxaban-30mg was ranked first for safety (SUCRA: 93.3). Dabigatran-110mg/150mg, and apixaban-5mg were regarded as the most effective and reasonably safe interventions in the trade-off analysis. Regarding mild renal impairment, edoxaban-60mg was ranked first for efficacy (SUCRA: 97.8), and edoxaban-30mg was ranked first for safety (SUCRA: 99.5). Edoxaban-60mg and dabigatran-150mg were accounted as the most effective and reasonably safe interventions. With regards to moderate renal impairment, dabigatran-150mg was ranked first for efficacy (SUCRA: 95.1), and edoxaban-15mg was ranked first for safety (SUCRA: 98.2). Apixaban-2.5mg and Edoxaban-30mg was considered as the reasonably effective and the safest interventions. Conclusions Dabigatran-150mg seems the most effective therapy in patients with normal renal function and moderate renal impairment, and edoxaban-60mg in patients with mild renal impairment. Low dose edoxaban (15mg and 30mg) seems the safest intervention. Apixaban-2.5mg and edoxaban-30mg might be the best trade-off property in moderate renal insufficiency.